2013
DOI: 10.3846/1648715x.2013.807400
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Run Relationship Between House Prices and Inflation in South Africa: An Ardl Approach

Abstract: This paper investigates whether house prices provide a suitable hedge against inflation in South Africa by analysing the long-run relationship between house prices and the prices of non-housing goods and services. Quarterly data series are collected for the luxury, large middle-segment, medium middle-segment, small middle-segment and the entire middle segment of house prices, as well as, the consumer price index excluding housing costs for the period 1970:Q1-2011:Q1. Based on autoregressive distributed lag (AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
(31 reference statements)
3
9
0
Order By: Relevance
“…It was found that shocks in country risk components lasted longer in the large segment of the property market. This is consistent with Inglesi-Lotz and Gupta (2013) in which luxury housing segment was associated highest slope coefficient. Additionally, political risk has a short run effect on various segment of housing indices.…”
Section: Recommendations and Concluding Remarkssupporting
confidence: 89%
See 1 more Smart Citation
“…It was found that shocks in country risk components lasted longer in the large segment of the property market. This is consistent with Inglesi-Lotz and Gupta (2013) in which luxury housing segment was associated highest slope coefficient. Additionally, political risk has a short run effect on various segment of housing indices.…”
Section: Recommendations and Concluding Remarkssupporting
confidence: 89%
“…The article concluded that a long-run relationship existed between the housing market and the components of country risk, where the housing price indices increase with both economic and political risk but decrease with financial risk. Similar evidence in literature was Inglesi-Lotz and Gupta (2013) who established long run relationship among various housing segments and inflation. It was found that shocks in country risk components lasted longer in the large segment of the property market.…”
Section: Recommendations and Concluding Remarkssupporting
confidence: 81%
“…The ARDL approach has been used by several researchers to analyse housing market dynamics (e.g., Bangura & Lee, 2020) and to test the relationship between house prices and other economic and political variables (e.g., Apergis et al, 2015;Inglesi-Lotz & Gupta, 2013).…”
Section: Modelmentioning
confidence: 99%
“…Thus we hypothesize two-way causality between GDP and property prices. Inglesi-Lotz et al (2013) state that house prices in South Africa provide a stable, but quantitatively minor, inflation hedge in the long-run; hence, a one way causality between inflation as measured by changes in the WPI to property prices is hypothesized. Lipscomb et al (2003) study real estate prices in Mexico, and believe that the increase in real estate prices will lead to an increase in the exchange rate; however, with increases in the exchange rate, real estate prices increase even more so.…”
Section: Relationship Between Macroeconomic Variables and Property Pricesmentioning
confidence: 99%